Implikasi Metode Game Based Learning Pada Pembelajaran Mata Kuliah Kepramukaan Terhadap Mahasiswa PGMI - Nurul Ngainin Halim Kusuma Dwi Nur M Vika Aulia Lusiana (EDUTHINK: Jurnal Pemikiran Pendidikan Islam, 2022)
Scouting education is an extracurricular activity that must be followed by all students, both at the SD/MI level and SMA/MA level up to the university level. Likewise, at the Nahdlatul Ulama Islamic Institute of Tuban, the PGMI scouting study program is made a compulsory subject for students. The purpose of this study is to describe: 1) the steps in the application of the Game Based Learning Method in the learning of scouting courses for PGMI students, 2) the implications of the application of the Game Based Learning method in the learning of scouting courses for PGMI students. The approach in this study is a descriptive qualitative approach. Researchers collected data, using observation, interview and documentation techniques. The data analysis used is descriptive analysis using the Miles and Huberman model which is carried out in three stages, namely data reduction, data display, and conclusion drawing/verification. The results of this study indicate that it consists of six learning steps in applying the Game Based Learning method with the form of the King and Queen game, which in essence is a group formed to solve a problem related to the basic concept of scouting. Then using the term game King and Queen, if one of the groups is negligent, then it can be a consequence of answering questions. The implications of the application of this method are to make students more active, not bored, not sleepy, provide a meaningful learning experience, make learning fun, effective, efficient, foster learning motivation and improve learning outcomes in scouting courses.